Online foreign language teaching: challenges and solutions - Inessa K. Batenina; Yuliya M. Orekhova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper is devoted to the vital problem of foreign language teaching in the context of organizing online distance learning. The unfavorable epidemiological situation, modern political and economic transformations in the world have also had an impact on the sphere of education: online learning has received a powerful impetus for rapid development. Currently the digitalization of language education is one of the global trends, which is reflected in the requirements of the modernized Federal State Educational Standards of vocational and higher education. The development of digital didactics as a new essential branch of pedagogy touches upon the foreign language teaching process. At the same time, the implementation of innovations causes many difficulties and challenges for specialists who are used to traditional teaching methods and are trying to avoid reducing the quality of education. In this regard, the topic of this study is of particular relevance. The paper studies the benefits and drawbacks of foreign language teaching in educational institutions of various types, implemented with the help of distance technologies and modern teaching software. Both the teacher questionnaire and the survey made it possible to identify and describe in detail the advantages and disadvantages of conducting online classes in a foreign language in the Yaroslavl Town Planning College (Yaroslavl) and the Plekhanov Russian University of Economics (Moscow). The issue of increasing the effectiveness of the implementation of distant foreign language teaching was also considered by solving a number of methodological problems, such as the use of specific Internet discourse and clichs as part of communication in a foreign language at different class stages. The solution to this problem will let eliminate a number of psychological difficulties that all subjects of educational process face during online communication, and make communication more emotional.